Adoption of interorganizational system standards in supply chains An empirical analysis of RosettaNet standards - Chong, Alain Yee Loong; Ooi, Keng Boon (Emerald Group Publishing Limited, 2008)
Purpose – This study aims to empirically examine the factors that affect the adoption of RosettaNet standards. The four factors examined in this study are partners’ power, trust, products’ characteristics, and government influence. Design/methodology/approach – Original research using a self-administered questionnaire that was distributed to 400 Malaysian electrical and electronics (E&E) organizations. The hypotheses were tested by employing binary logistic regression analysis. Findings – The results show that partners’ power, trust, and products’ characteristics have significant and positive effects on the adoption of RosettaNet standards. Research limitations/implications – The generalisability of the findings is limited as the study focuses only on E&E industry in Malaysia. Practical implications – Organizations planning to adopt RosettaNet standards will be able to make managerial decisions based on the findings from this research. Originality/value – The findings made a contribution in terms of creating an understanding of the influence of the adoption ofRosettaNet standards.This studyhas filled previous research gap by advancing the understanding between the association of adoption factors and RosettaNet standards adoption.